Application of Real Option Analysis to Pharmaceutical R&D Project - ZHAI, JIN (2007)
Research and development (R&D) in pharmaceutical sector are characterized by long planning horizon, high uncertainty and irreversibility. A critical component in drug development is determining the financial value of the potential compound in the light of the substantial technical and economic uncertainty (Rogers et al, 2005). Given the well-know shortcomings of DCF, real option approach is considered to capture the substantial flexibility and value of strategy involve in the R&D project. Considerable efforts have been made in modeling of real R&D options given uncertainty and managerial flexibility as the key consideration.